Nietzsche: o corpo como expressão da vida enquanto fio condutor da vontade de poder - Pereira Neto, Euclides Silvestre (2017)
We developed the thematic of this master's thesis, that is linked to the Philosophical Phenomenology and Philosophical Hermeneutics Line in PPGH-UFPB, and we are receiving the Nietzschean suggestion and ―starting from the body and using it as a conducting wire" in a research that seeks to illustrate its perception of life as a demonstration of the will to power. In this perspective is possible to understand Nietzsche as a "philosopher of life," because from a conception of the body as an oligarchy of instinctual forces originated by the will to power is that he develops "a philosophy of instinct" as a creator of life. In this way, the observation of the body in its new paradigmatic field of research, because as an object and tool of philosophical inquiry it would allow to make a reduction of all organic functions for the will to power. With this physiological perspective, Nietzsche's thought seeks to dissipate the obscurity of the transcendental presuppositions of the metaphysical tradition, which denies the sensitive life any value of truth for the sake of a supposed life in another world, affirming the tragic existence as foundation of a conception of healthy life as a phenomenon of the will to potency. To clarify this comprehension we chose to write small philosophical essays that analyze the particular meaning of the manifold terms that Nietzsche uses to constitute his vision of the body as conducting wire of life as a will to power. Thus, as a joint these essays demonstrate the evolution of the conception of body, life and the will to power in Nietzschean thinking, especially when characterizing his understanding and development status in specific context of each work and when they are being presented.